Investigating Nomophobia as a Predictor of Smartphone Addiction among Nigerian Pre-service Mathematics Teachers - AWOFALA, ADENEYE OLAREWAJU (Universitas Sebelas Maret, 2020)
Nomophobia and smartphone addiction are behavioural disorders that are maladaptive and affect 21st-century digital natives anywhere, everywhere. This study investigated nomophobia as a predictor of smartphone addiction among Nigerian pre-service mathematics teachers within the framework of quantitative methodology of non-experimental correlational research design. The participants consisted of 300 pre-service mathematics teachers randomly selected from the Department of Science and Technology Education, University of Lagos, Nigeria. Four research questions were answered in the study using the statistical tools of frequency, percentage, mean, standard deviation, Pearson product-moment correlation coefficient, and multiple regression analysis. Results showed that majority of the pre-service mathematics suffered from nomophobia and smartphone addiction. There was a positive relationship between smartphone addiction and nomophobia and nomophobia was a significant predictor of smartphone addiction among pre-service mathematics teachers. Based on these findings it was concluded that universities and parents in Nigeria should find a way of reducing the prevalence of nomophobia and smartphone addiction in pre-service mathematics teachers in the country.